What is a data space—Logical architecture modelDSSC - Juha-Pekka Soininen; Gabriella Laatikainen (Data in Brief)
The paper presents a use case model and a logical architecture model of a data space system. The models view the data space system from the user and operator perspectives and describe the needed functionalities and their connection on an abstract level. The core features in our data space model are collaboration networks and contract-based data sharing. The models are meant as a simple and explainable first introduction to what a data space system is, and they provide an implementation technology-independent basis for creating data space implementation specifications. The model is validated by comparing it with existing data space reference models from IDSA, GAIA-X, and the Data Space Support Centre. The modelled core features map with the technical specifications of the system. Our study enables data space system developers to think out of the box and create new innovative solutions.